2012
DOI: 10.1007/s00216-012-5800-6
|View full text |Cite
|
Sign up to set email alerts
|

DART-Orbitrap MS: a novel mass spectrometric approach for the identification of phenolic compounds in propolis

Abstract: This is the first direct analysis in real-time mass spectrometry (DART-MS) study of propolis and a first study on the analysis of bee products using high-resolution DART-MS (DART-HRMS). Identification of flavonoids and other phenolic compounds in propolis using direct analysis in real-time coupling with Orbitrap mass spectrometry (DART-Orbitrap MS) was performed in the negative ion mode for minimizing the matrix effects, while the positive ion mode was used for the confirmation of selected compounds. Possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 19 publications
(30 reference statements)
0
21
0
Order By: Relevance
“…Negative ionization mode was employed, because the matrix influence is reduced in this mode due to the selective ionization of the target phenolic compounds . The average reproducibility of peak areas for the selected ion chronogram of the deprotonated naringenin molecule at m / z 271.0609–271.0618 was ca.…”
Section: Resultsmentioning
confidence: 99%
“…Negative ionization mode was employed, because the matrix influence is reduced in this mode due to the selective ionization of the target phenolic compounds . The average reproducibility of peak areas for the selected ion chronogram of the deprotonated naringenin molecule at m / z 271.0609–271.0618 was ca.…”
Section: Resultsmentioning
confidence: 99%
“…Ni: not identified.Tr: traces.*a: confirmed by standard; b: confirmed by reference [41, 42]; c: confirmed by MS fragmentation.**d: expressed as cinnamic acid; e: expressed as ferulic acid; f: expressed as caffeic acid; g: expressed as p -coumaric acid; h: expressed as apigenin.…”
Section: Figurementioning
confidence: 98%
“…For instance, Liu's research team reported its application to the rapid determination of triazine herbicides in water [10]. Chernetsova and collaborators used DART MS to identify phenolic compounds in propolis [14]. Although many types of analytes have been studied, information on analyzing monosaccharides and disaccharides using DART MS is limited [15].…”
mentioning
confidence: 99%